Non-sulfonated calcium chloride water-based drilling fluid and preparation method thereof

By developing a non-sulfonated calcium chloride water-based drilling fluid, using composite modified starch and modified nanomontmorillonite and other components, the existing drilling fluid has been solved under high mudstone pollution. Problem, stable rheology and efficient suppression performance over a wide temperature and density range are achieved.

CN119463823APending Publication Date: 2025-02-18YANGTZE UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411700924.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing calcium chloride drilling fluid has a high concentration of mudstone pollution, and the content of sulfonated materials is not environmentally friendly, the scope of application is narrow, and the risk of well leakage is high.

Method used

Develop a non-sulfonated calcium chloride water-based drilling fluid, which includes water, calcium chloride, pH regulator, free radical scavenger, filter reduction loss agent, sealing agent, flow regulator, lubricant and heavy The mixture of crystals, using composite modified starch and modified nanomontmorillonite, ensures that the drilling fluid is stable in a wide temperature and density range.

Benefits of technology

The drilling fluid exhibits significant clay hydration inhibitory performance in high-temperature and mudstone formations, reducing the risk of well wall expansion instability and drilling chip hydration slurry, improving drilling efficiency, and reducing the risk of sulfonated materials due to the absence of sulfonated materials environmental pollution risk.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005154043270000221
    Figure BDA0005154043270000221
  • Figure BDA0005154043270000222
    Figure BDA0005154043270000222
  • Figure BDA0005154043270000231
    Figure BDA0005154043270000231
Patent Text Reader

Abstract

The invention provides a non-sulfonated calcium chloride water-based drilling fluid and a preparation method thereof, and particularly relates to the technical field of oil field drilling fluids. The non-sulfonated calcium chloride water-based drilling fluid provided by the invention is prepared from the following components in parts by mass: 100 parts of water, 5-35 parts of calcium chloride, 0.5-2.5 parts of a pH regulator, 3.5-6.5 parts of a free radical scavenger, 1.5-3.5 parts of a filtrate reducer, 2.5-5.5 parts of a blocking agent, 0.5-1.5 parts of a flow pattern regulator, 1.5-3.5 parts of a lubricant and a plurality of barite, the filtrate reducer is composite modified starch; the flow pattern regulator is prepared from modified nano montmorillonite, nano hectorite and diidine gum; the lubricant comprises oleic acid imidazoline, polyethylene glycol borate, poly alpha olefin and nano polytetrafluoroethylene. The drilling fluid prepared by the invention does not contain a sulfonated material, and is environment-friendly and strong in inhibition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oilfield drilling fluid, and in particular relates to a non-sulfonated calcium chloride water-based drilling fluid and a preparation method thereof. Background Art

[0002] In order to speed up the process of oil and gas development, drilling speed increase is the key. With the increase of mechanical drilling speed, more and more problems are coming, such as the instability of the wellbore in water-sensitive mudstone formations and the difficulty in controlling the rheology of drilling fluids. In the case of insufficient inhibition of drilling fluids, the wellbore of mudstone formations is prone to instability and collapse due to expansion, causing complex downhole accidents. Although oil-based drilling fluids have strong inhibition, they will cause environmental pollution and are costly; traditional polymer / potassium chloride water-based drilling fluids have limited resistance to mudstone pollution, and in the case of high-concentration mudstone pollution, the problem of excessively fast viscosity rise will still occur. Calcium chloride drilling fluids have high concentrations of calcium ions. On the one hand, they can reduce the clay slurrying ability by converting sodium soil into calcium soil, and on the other hand, they can suppress its dispersion by compressing the double electric layer on the surface of clay particles. Therefore, for highly water-sensitive formations with high clay content such as mudstone, calcium chloride drilling fluids can effectively inhibit the instability of wellbore expansion and the hydration of drill cuttings to make slurry, thereby reducing complex downhole accidents and improving drilling efficiency.

[0003] Although the calcium chloride drilling fluids described in the prior art have good inhibition and lubrication properties, they all contain sulfonated materials, are environmentally unfriendly, and have problems such as low temperature or density resulting in a narrow application range, and high viscosity and shearing resulting in a high risk of well leakage. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a non-sulfonated calcium chloride water-based drilling fluid and a preparation method thereof. The non-sulfonated calcium chloride water-based drilling fluid prepared by the present invention does not contain sulfonated materials, is environmentally friendly, has stable rheology in a wide temperature and density range, has low filtration loss, good lubricity, and strong inhibition performance.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The present invention provides a non-sulfonated calcium chloride water-based drilling fluid, which comprises, by weight, 100 parts of water, 5 to 35 parts of calcium chloride, 0.5 to 2.5 parts of a pH regulator, 3.5 to 6.5 parts of a free radical scavenger, 1.5 to 3.5 parts of a fluid loss reducer, 2.5 to 5.5 parts of a plugging agent, 0.5 to 1.5 parts of a flow pattern regulator, 1.5 to 3.5 parts of a lubricant and a plurality of barites;

[0007] The fluid loss reducer is a composite modified starch;

[0008] The composite modified starch contains carboxyl, amide, pyrrolidone five-membered ring and lauryl;

[0009] The flow pattern regulator comprises the following components based on 100 parts by mass: 40 to 60 parts of modified nano-montmorillonite, 20 to 30 parts of nano-hectorite and 20 to 30 parts of diutanol;

[0010] The modified nano-montmorillonite comprises nano-montmorillonite and carboxyl groups, amide groups and pyrrolidone five-membered rings grafted on the surface of the nano-montmorillonite;

[0011] The lubricant comprises the following components based on 100 parts by mass: 50-60 parts of oleic acid imidazoline, 20-30 parts of polyethylene glycol borate, 5-20 parts of polyalphaolefin and 5-10 parts of nano polytetrafluoroethylene.

[0012] Preferably, the free radical scavenger comprises the following components based on 100 parts by mass: 60 to 80 parts by mass of potassium formate and 20 to 40 parts by mass of sodium formate;

[0013] The pH regulator comprises the following components based on 100 parts by mass: 60 to 80 parts by mass of magnesium oxide and 20 to 40 parts by mass of magnesium hydroxide.

[0014] Preferably, the plugging agent comprises the following components based on 100 parts by mass: 40-60 parts of potassium humate and 40-60 parts of ultrafine calcium carbonate.

[0015] Preferably, the potassium humate comprises the following components based on 100 parts by mass: 60 to 80 parts of potassium humate and 20 to 40 parts of potassium humate;

[0016] The ultrafine calcium carbonate comprises the following components based on 100 parts by mass: 20-30 parts of 1000-mesh calcium carbonate, 20-30 parts of 2000-mesh calcium carbonate, 20-30 parts of 3000-mesh calcium carbonate and 20-30 parts of 4000-mesh calcium carbonate.

[0017] Preferably, the oleic acid imidazoline is prepared from vegetable oleic acid and polyethylene polyamine by amidation and cyclization.

[0018] Preferably, the preparation of the modified nano-montmorillonite comprises:

[0019] Mixing 150 to 200 parts of an alcohol aqueous solution and 1 to 3 parts of vinyltriethoxysilane by weight, adjusting the pH to 2 to 5, and performing a hydrolysis reaction to obtain a hydrolysis product;

[0020] The hydrolyzate is mixed with 8 to 12 parts of nano-montmorillonite to carry out a silane coupling reaction to obtain silane-coupled nano-montmorillonite;

[0021] 100-150 parts of water, 2-4 parts of itaconic acid, 3-5 parts of N,N-dimethylacrylamide and 4-6 parts of N-vinyl-2-pyrrolidone are mixed, the pH is adjusted to 7-9, the silane-coupled nano-montmorillonite is added, the mixture is heated to 60-70° C., 0.1-0.2 parts of initiator are added, and graft copolymerization is performed to obtain the modified nano-montmorillonite.

[0022] Preferably, the preparation of the composite modified starch comprises:

[0023] 8 to 12 parts of lauryl amine are heated and mixed with 3 to 5 parts of maleic anhydride to carry out an amidation reaction to obtain an amidation product;

[0024] Mix 30-40 parts of starch and 100-200 parts of water, heat to 70-90°C, cool, add 5-7 parts of alkali and 30-60 parts of alcohol aqueous solution, heat to 40-50°C, add 25-55 parts of monochloroacetic acid-alcohol aqueous solution, carry out etherification reaction, and obtain carboxymethyl starch;

[0025] The amidation product is mixed with 100-150 parts of water and 3-5 parts of N-vinyl-2-pyrrolidone, the carboxymethyl starch is added, the mixture is heated to 60-70° C., and 0.5-1.0 parts of azobisisobutyramidine hydrochloride is added to initiate polymerization reaction to obtain composite modified starch.

[0026] Preferably, the mass content of amylose in the starch is ≥40%.

[0027] Preferably, the density of the non-sulfonated calcium chloride water-based drilling fluid is 1.0-1.8 g / cm 3 .

[0028] The present invention also provides a method for preparing the non-sulfonated calcium chloride water-based drilling fluid described in the above technical solution, comprising the following steps:

[0029] The non-sulfonated calcium chloride water-based drilling fluid is obtained by mixing water, calcium chloride, a pH regulator, a free radical scavenger, a fluid loss reducer, a plugging agent, a flow pattern regulator, a lubricant and barite.

[0030] The invention provides a non-sulfonated calcium chloride water-based drilling fluid, which comprises, by weight, 100 parts of water, 5 to 35 parts of calcium chloride, 0.5 to 2.5 parts of a pH regulator, 3.5 to 6.5 parts of a free radical scavenger, 1.5 to 3.5 parts of a fluid loss reducer, 2.5 to 5.5 parts of a plugging agent, 0.5 to 1.5 parts of a flow pattern regulator, 1.5 to 3.5 parts of a lubricant and a plurality of barites; the fluid loss reducer is a composite modified starch; the composite modified starch contains a carboxyl group, an amide group, a pyrrolidone five-membered ring and a long-chain alkane. The flow pattern regulator comprises the following components based on 100 parts by mass: 40-60 parts of modified nano-montmorillonite, 20-30 parts of nano-hectorite and 20-30 parts of diutanol; the modified nano-montmorillonite comprises nano-montmorillonite and carboxyl groups, amide groups and pyrrolidone five-membered rings grafted on the surface of the nano-montmorillonite through a silane coupling agent; the lubricant comprises the following components based on 100 parts by mass: 50-60 parts of oleic acid imidazoline, 20-30 parts of polyethylene glycol borate, 5-20 parts of polyalphaolefin and 5-10 parts of nano-polytetrafluoroethylene. The flow pattern regulator used in the present invention is composed of modified nano-montmorillonite, nano-hectorite and diutan gum. The modified nano-montmorillonite contains a large number of carboxyl groups, amide groups and pyrrolidone five-membered ring structures. On the one hand, the charge density is increased to effectively alleviate the compression effect of divalent cations on the diffusion double layer of montmorillonite. On the other hand, the hydrogen bond interaction between molecules is improved, and the ability to build a spatial network structure is strengthened, so that the montmorillonite has excellent shear thinning characteristics in high-calcium salt water and can significantly improve the rheology of calcium chloride drilling fluid. In addition, the pyrrolidone five-membered ring structure can also increase the spatial steric hindrance to maintain the stability of the network structure at high temperature. Lithium ions in the nano-hectorite are not easy to migrate out of the lattice structure, and the structural integrity can be maintained at a higher temperature, thereby further improving the thermal stability. Diutan gum is a microbial polysaccharide polymer with good salt, calcium and temperature resistance. It is compounded with the modified nano-montmorillonite and the nano-hectorite. It can significantly improve the dynamic-plastic ratio of calcium chloride drilling fluid, which is beneficial to suspending cuttings and improving the wellbore cleaning effect; composite modified starch is used as a fluid loss reducer, and the composite modified starch contains a large number of carboxyl groups, amide groups, pyrrolidone five-membered rings and lauryl groups. The carboxyl groups and amide groups give the fluid loss reducer good hydrophilicity and strong adsorption, and can be effectively adsorbed on the surface of solid phase particles and participate in the formation of mud cakes, thereby improving the density and wall protection. The introduction of carboxyl groups can also increase the charge density of the fluid loss reducer, thereby reducing the salt shielding effect in high-concentration electrolytes, which helps to improve the calcium resistance. The long-chain alkane (lauryl) side chains provide certain hydrophobic properties, which can form a hydrophobic film on the surface of the mud cake, further preventing water molecules from penetrating, thereby reducing the fluid loss. In addition, the pyrrolidone five-membered ring helps to enhance steric hindrance and inhibit the hydrolysis of the amide group, which helps to improve the thermal stability and high-temperature hydrolysis resistance of the fluid loss reducer.

[0031] In addition, the oleic acid imidazoline in the lubricant used in the present invention contains nitrogen heterocycles and hydrocarbon long chains, which can form a strong adsorption lubricating film on the metal surface, thereby reducing the friction coefficient; the polyethylene glycol borate can provide a sliding interface and reduce the direct contact between the friction pairs, and has excellent thermal stability due to the presence of the borate; the polyalphaolefin has good resistance to thermal degradation, is conducive to forming a stable lubricating oil film, and is biodegradable; nano polytetrafluoroethylene, as a solid lubricant, can continuously fill tiny pits on the surface during the friction process, form a smooth surface, and improve the wear resistance of the lubricating film.

[0032] The non-sulfonated calcium chloride water-based drilling fluid provided by the present invention has, on the one hand, significant clay hydration inhibition performance, and can effectively prevent hydration expansion of mudstone well wall and hydration slurrying of mudstone cuttings, thereby maintaining the wellbore stability and rheological stability of the high mudstone formation, which helps to improve the drilling efficiency; on the other hand, it has a wide temperature and density application range, and can meet the requirements of most mudstone well sections for the temperature resistance and density control of the drilling fluid; in addition, it also has excellent water loss wall-forming and lubrication and drag reduction properties, and does not contain sulfonated materials, which reduces the difficulty of drilling fluid waste treatment and avoids environmental pollution problems.

[0033] The results of the examples show that the density of the non-sulfonated calcium chloride water-based drilling fluid prepared by the present invention can reach up to 1.80 g / cm 3 , with a maximum temperature resistance of 150°C and excellent rheological properties, dynamic-plastic ratio>0.6, API filtration loss<3.5mL, HTHP filtration loss<13mL, extreme pressure friction coefficient≤0.08, apparent viscosity increase rate after 40% sodium-based bentonite contamination≤40%, mudstone rolling recovery rate>90%, clay linear expansion rate<10%, biodegradation index>18%, and dry basis (excluding barite and calcium chloride) sulfur content is 0. While meeting the safety operation requirements of high-temperature and high-mudstone formations, it also has significant environmental protection and biodegradability. DETAILED DESCRIPTION

[0034] The present invention provides a non-sulfonated calcium chloride water-based drilling fluid, which comprises, by weight, 100 parts of water, 5 to 35 parts of calcium chloride, 0.5 to 2.5 parts of a pH regulator, 3.5 to 6.5 parts of a free radical scavenger, 1.5 to 3.5 parts of a fluid loss reducer, 2.5 to 5.5 parts of a plugging agent,

[0035] 0.5-1.5 parts of flow pattern regulator, 1.5-3.5 parts of lubricant and some barite;

[0036] The fluid loss reducer is a composite modified starch;

[0037] The composite modified starch contains carboxyl, amide, pyrrolidone five-membered ring and long-chain alkane;

[0038] The flow pattern regulator comprises the following components based on 100 parts by mass: 40 to 60 parts of modified nano-montmorillonite, 20 to 30 parts of nano-hectorite and 20 to 30 parts of diutanol;

[0039] The modified nano-montmorillonite comprises nano-montmorillonite and carboxyl groups, amide groups and pyrrolidone five-membered rings grafted on the surface of the nano-montmorillonite through a silane coupling agent;

[0040] The lubricant comprises the following components based on 100 parts by mass: 50-60 parts of oleic acid imidazoline, 20-30 parts of polyethylene glycol borate, 5-20 parts of polyalphaolefin and 5-10 parts of nano polytetrafluoroethylene.

[0041] In the present invention, unless otherwise specified, the raw materials and equipment used are commercially available products well known in the art.

[0042] The non-sulfonated calcium chloride water-based drilling fluid includes 0.5 to 1.5 parts of a flow pattern regulator in parts by mass. In a specific implementation, the flow pattern regulator may be 0.5 parts, 0.8 parts, 1 parts, 1.2 parts or 1.5 parts.

[0043] Taking the mass parts of the flow pattern regulator as 100, the flow pattern regulator in the present invention comprises the following components: 40-60 parts of modified nano-montmorillonite, 20-30 parts of nano-hectorite and 20-30 parts of diutan. In the specific implementation, the nano-hectorite can be 20 parts, 22 parts, 25 parts, 27 parts or 30 parts, the diutan can be 20 parts, 22 parts, 25 parts, 27 parts or 30 parts, and the modified nano-montmorillonite can be 40 parts, 46 parts, 48 ​​parts, 51 parts, 53 parts, 54 parts, 50 parts or 60 parts.

[0044] The modified nano-montmorillonite is described below.

[0045] The modified nano-montmorillonite comprises nano-montmorillonite and carboxyl groups, amide groups and pyrrolidone five-membered rings grafted on the surface of the nano-montmorillonite through a silane coupling agent.

[0046] In the present invention, the preparation of the modified nano-montmorillonite preferably includes:

[0047] Mixing 150 to 200 parts of an alcohol aqueous solution and 1 to 3 parts of vinyltriethoxysilane by weight, adjusting the pH to 2 to 5, and performing a hydrolysis reaction to obtain a hydrolysis product;

[0048] The hydrolyzate is mixed with 8 to 12 parts of nano-montmorillonite to carry out a silane coupling reaction to obtain silane-coupled nano-montmorillonite;

[0049] 100-150 parts of water, 2-4 parts of itaconic acid, 3-5 parts of N,N-dimethylacrylamide and 4-6 parts of N-vinyl-2-pyrrolidone are mixed, the pH is adjusted to 7-9, the silane-coupled nano-montmorillonite is added, the mixture is heated to 60-70° C., 0.1-0.2 parts of initiator are added, and graft copolymerization is performed to obtain the modified nano-montmorillonite.

[0050] In the present invention, 150 to 200 parts of an alcohol aqueous solution and 1 to 3 parts of vinyltriethoxysilane are mixed by weight, the pH value is adjusted to 2 to 5, and a hydrolysis reaction is carried out to obtain a hydrolysis product.

[0051] In parts by mass, the present invention preferably uses 150 to 200 parts of alcohol aqueous solution. In specific implementation operations, the alcohol aqueous solution can be 150 parts, 160 parts, 170 parts, 175 parts, 180 parts, 190 parts or 200 parts.

[0052] Taking the alcohol aqueous solution as 100 parts by mass, the alcohol aqueous solution in the present invention preferably includes the following components: 80-90 parts of anhydrous ethanol and 10-20 parts of deionized water; in the specific implementation operation, the anhydrous ethanol can be 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 87 parts, 88 parts or 90 parts; in the specific implementation operation, the deionized water can be 10 parts, 12 parts, 13 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts.

[0053] Based on the mass fraction of the alcohol aqueous solution, the present invention preferably uses 1 to 3 parts of vinyltriethoxysilane. In the specific implementation operation, the vinyltriethoxysilane can be 1 part, 1.2 parts, 1.5 parts, 2 parts, 2.3 parts, 2.5 parts or 3 parts.

[0054] The present invention has no special requirements on the mixing method, and the commonly used technical means of the present invention can be used, for example, stirring.

[0055] In the present invention, the pH is preferably adjusted to 2-5. In specific implementations, the pH may be 2, 3, 4 or 5. In the present invention, 0.1 mol / L hydrochloric acid is preferably used to adjust the pH to 2-5.

[0056] In the present invention, the pH adjustment preferably further includes nitrogen deoxygenation.

[0057] In the present invention, the temperature of the hydrolysis reaction is preferably 50-60°C. In the specific implementation, the temperature of the hydrolysis reaction can be 50°C, 52°C, 54°C, 55°C, 56°C, 58°C or 60°C; the time of the hydrolysis reaction is preferably 4-6h. In the specific implementation, the time of the hydrolysis reaction can be 4h, 4.5h, 5h, 5.5h or 6h.

[0058] The hydrolysis product is obtained. In the present invention, the hydrolysis product is mixed with 8 to 12 parts of nano-montmorillonite to carry out a silane coupling reaction to obtain silane-coupled nano-montmorillonite.

[0059] Based on the mass fraction of the alcohol aqueous solution, the present invention preferably uses 8 to 12 parts of nano-montmorillonite. In the specific implementation operation, the nano-montmorillonite can be 8 parts, 9 parts, 10 parts, 11 parts or 12 parts.

[0060] In the present invention, the temperature of the silane coupling reaction is preferably 60-70°C, and the time is preferably 10-16h. In the specific implementation operation, the temperature of the silane coupling reaction can be 60°C, 62°C, 64°C, 65°C, 66°C, 68°C or 70°C; in the specific implementation operation, the time of the silane coupling reaction can be 10h, 11h, 12h, 13h, 14h, 15h or 16h.

[0061] In the present invention, after the silane coupling reaction, the process preferably further comprises: solid-liquid separation of the obtained product liquid, washing with an alcohol solvent, drying and crushing.

[0062] The present invention has no special requirements on the method of solid-liquid separation, and the commonly used technical means of the present invention can be adopted, for example, vacuum distillation, centrifugation, filtration, etc.

[0063] In the present invention, the alcohol solvent in the alcohol solvent washing is preferably anhydrous ethanol, and the number of times of washing is preferably 2 to 3 times.

[0064] The present invention has no special requirements on the drying method, and the commonly used technical means of the present invention can be adopted, for example, vacuum drying.

[0065] The present invention has no special requirements on the method of the pulverization, and the commonly used technical means of the present invention can be adopted, such as grinding, ball milling, etc.

[0066] After obtaining the silane-coupled nano-montmorillonite, the present invention mixes 100 to 150 parts of water, 2 to 4 parts of itaconic acid, 3 to 5 parts of N,N-dimethylacrylamide and 4 to 6 parts of N-vinyl-2-pyrrolidone, adjusts the pH to 7 to 9, adds the silane-coupled nano-montmorillonite, heats to 60 to 70° C., adds 0.1 to 0.2 parts of an initiator, and performs graft copolymerization to obtain the modified nano-montmorillonite.

[0067] Based on the mass fraction of the alcohol aqueous solution, the present invention preferably uses 100 to 150 parts of water. In the specific implementation operation, the water can be 100 parts, 110 parts, 120 parts, 130 parts, 140 parts or 150 parts.

[0068] Based on the mass fraction of the alcohol aqueous solution, the present invention preferably uses 2 to 4 parts of itaconic acid. In the specific implementation operation, the itaconic acid can be 2 parts, 2.5 parts, 3 parts, 3.5 parts or 4 parts.

[0069] Based on the mass fraction of the alcohol aqueous solution, the present invention preferably uses 3 to 5 parts of N,N-dimethylacrylamide. In the specific implementation operation, the N,N-dimethylacrylamide can be 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts.

[0070] Based on the mass fraction of the alcohol aqueous solution, the present invention preferably uses 4 to 6 parts of N-vinyl-2-pyrrolidone. In the specific implementation operation, the N-vinyl-2-pyrrolidone can be 4 parts, 4.5 parts, 5 parts, 5.5 parts or 6 parts.

[0071] In the present invention, the pH is preferably adjusted to 7-9. In specific implementations, the pH may be 7, 8 or 9. In the present invention, it is preferred to use 0.1 mol / L potassium hydroxide solution to adjust the pH to 7-9.

[0072] In the present invention, stirring is preferably performed before adjusting the pH, and the stirring time is preferably 10 to 30 minutes. In the specific implementation operation, the stirring time can be 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes.

[0073] In the present invention, the step of adding the silane-coupled nano-montmorillonite preferably further comprises deoxygenation by passing nitrogen.

[0074] In the present invention, it is preferably heated to 60-70°C. In a specific implementation, it can be heated to 60°C, 63°C, 65°C, 67°C or 70°C.

[0075] Based on the mass fraction of the alcohol aqueous solution, the present invention preferably uses 0.1 to 0.2 parts of initiator. In the specific implementation operation, the initiator can be 0.1 parts, 0.12 parts, 0.15 parts, 0.18 parts or 0.2 parts.

[0076] Based on 100 parts by mass of the initiator, the initiator in the present invention preferably includes the following components: 40 to 60 parts of potassium persulfate and 40 to 60 parts of ammonium persulfate; in the specific implementation, the potassium persulfate can be 40 parts, 43 parts, 45 parts, 48 ​​parts, 50 parts, 53 parts, 55 parts, 58 parts or 60 parts; in the specific implementation, the ammonium persulfate can be 40 parts, 43 parts, 45 parts, 48 ​​parts, 50 parts, 53 parts, 55 parts, 58 parts or 60 parts.

[0077] In the present invention, the temperature of the graft copolymerization is preferably 60-80°C, and the time is preferably 4-6h; in the specific implementation operation, the temperature of the silane coupling reaction can be 60°C, 62°C, 65°C, 70°C, 75°C or 80°C; in the specific implementation operation, the time of the silane coupling reaction can be 4h, 4.5h, 5h, 5.5h or 6h.

[0078] In the present invention, after the graft copolymerization, the process preferably further comprises: solid-liquid separation of the obtained product liquid, washing with an alcohol solvent, drying and crushing.

[0079] The modified nano-montmorillonite obtained by the present invention introduces a large number of carboxyl groups, amide groups and pyrrolidone five-membered rings on the basis of nano-montmorillonite by using a silane coupling agent as a connection point, which, on the one hand, increases the charge density and can effectively alleviate the compression effect of divalent cations on the diffusion double layer of montmorillonite; on the other hand, it increases the hydrogen bond interaction between molecules, strengthens the ability to build a spatial network structure, and enables the modified nano-montmorillonite to have excellent shear-thinning properties in high-calcium salt water, and can significantly improve the rheology of calcium chloride drilling fluid; in addition, the pyrrolidone five-membered ring can also increase the steric hindrance to maintain the stability of the network structure at high temperature.

[0080] The flow pattern regulator provided by the present invention introduces nano-hectorite on the basis of modified nano-montmorillonite. Lithium ions in nano-hectorite are not easy to migrate out of the lattice structure, and the structural integrity can be maintained at a higher temperature, further improving the thermal stability of the drilling fluid. Diutan gum is a microbial polysaccharide polymer with good salt, calcium and temperature resistance. It can significantly improve the dynamic plastic ratio of calcium chloride drilling fluid when compounded with modified nano-montmorillonite and nano-hectorite, which is beneficial to suspending rock cuttings and improving the wellbore cleaning effect. In addition, the materials used are non-toxic and tasteless, which is beneficial to ecological environmental protection.

[0081] Based on the mass fraction of the flow pattern regulator, the non-sulfonated calcium chloride water-based drilling fluid includes 1.5 to 3.5 parts of a fluid loss reducer. In a specific implementation, the fluid loss reducer may be 1.5 parts, 1.8 parts, 2 parts, 1.2 parts, 1.5 parts, 2.8 parts, 3 parts or 3.5 parts.

[0082] In the present invention, the fluid loss reducer is a composite modified starch; the composite modified starch contains a carboxyl group, an amide group, a pyrrolidone five-membered ring and a lauryl group.

[0083] The composite modified starch is described below.

[0084] In the present invention, the preparation of the composite modified starch preferably comprises:

[0085] 8 to 12 parts of lauryl alcohol are heated and mixed with 3 to 5 parts of maleic anhydride to carry out an amidation reaction to obtain an amidation product;

[0086] Mix 30-40 parts of starch and 100-200 parts of water, heat to 70-90°C, cool, add 5-7 parts of alkali and 30-60 parts of alcohol aqueous solution, heat to 40-50°C, add 25-55 parts of monochloroacetic acid-alcohol aqueous solution, and cause etherification reaction to obtain carboxymethyl starch;

[0087] The amidation product is mixed with 100-150 parts of water and 3-5 parts of N-vinyl-2-pyrrolidone, the carboxymethyl starch is added, the mixture is heated to 60-70° C., and 0.5-1.0 parts of azobisisobutyramidine hydrochloride is added to initiate polymerization reaction to obtain composite modified starch.

[0088] The invention heats 8 to 12 parts of lauryl alcohol and mixes them with 3 to 5 parts of maleic anhydride to carry out an amidation reaction to obtain an amidation product.

[0089] In terms of parts by mass, the present invention preferably uses 8 to 12 parts of lauryl alcohol. In a specific implementation, the lauryl alcohol can be 8 parts, 10 parts, 11 parts or 12 parts.

[0090] In the present invention, the temperature at which the lauryl alcohol is heated is preferably 60-70°C. In a specific implementation, the temperature at which the lauryl alcohol is heated can be 60°C, 62°C, 65°C, 67°C, 69°C or 70°C.

[0091] Based on the mass fraction of the lauryl alcohol, the present invention preferably uses 3 to 5 parts of maleic anhydride. In the specific implementation, the maleic anhydride can be 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts.

[0092] In the present invention, nitrogen is preferably passed through to remove oxygen before the amidation reaction.

[0093] In the present invention, the temperature of the amidation reaction is preferably 60-80°C, and the time is preferably 4-6h. In the specific implementation operation, the temperature of the amidation reaction can be 60°C, 62°C, 65°C, 70°C, 75°C or 80°C; in the specific implementation operation, the time can be 4h, 4.5h, 5h, 5.5h or 6h.

[0094] The method comprises the following steps: mixing 30-40 parts of starch and 100-200 parts of water, heating the mixture to 70-90° C., cooling the mixture, adding 5-7 parts of alkali and 30-60 parts of an alcohol aqueous solution, heating the mixture to 40-50° C., adding 25-55 parts of a monochloroacetic acid-alcohol aqueous solution, and causing an etherification reaction to obtain carboxymethyl starch.

[0095] Based on the mass fraction of the lauryl alcohol, the present invention preferably uses 30 to 40 parts of starch. In the specific implementation, the starch can be 30 parts, 32 parts, 35 parts, 38 parts or 40 parts. In the present invention, the mass content of amylose in the starch is preferably ≥40%. In the specific implementation, the mass content of amylose in the starch can be 40%, 50%, 60%, 70%, 80% or 90%.

[0096] Based on the mass fraction of the lauryl alcohol, the present invention preferably uses 100 to 200 parts of water. In the specific implementation operation, the water can be 100 parts, 120 parts, 150 parts, 180 parts or 200 parts.

[0097] In the present invention, the starch and water are preferably heated to 70-90°C. In a specific implementation, the starch and water can be heated to 70°C, 75°C, 80°C, 85°C or 90°C. The heating time is preferably 2-4h. In a specific implementation, the heating time can be 2h, 3h or 4h. The starch and water are heated to obtain a colloidal solution.

[0098] Based on the mass fraction of the lauryl alcohol, the present invention preferably uses 5 to 7 parts of alkali. In the specific implementation, the alkali can be 5 parts, 6 parts or 7 parts. In the present invention, the alkali is preferably sodium hydroxide.

[0099] Based on the mass fraction of the lauryl alcohol, the present invention preferably uses 30 to 60 parts of alcohol aqueous solution. In the specific implementation operation, the alcohol aqueous solution can be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts or 60 parts.

[0100] In the present invention, the heating temperature is preferably 40-50°C. In a specific implementation, the heating temperature may be 40°C, 43°C, 46°C, 48°C or 50°C.

[0101] Based on the mass fraction of the lauryl alcohol, the present invention preferably uses 25 to 55 parts of monochloroacetic acid-alcohol aqueous solution. In the specific implementation operation, the monochloroacetic acid-alcohol aqueous solution can be 25 parts, 32 parts, 35 parts, 40 parts, 52 parts or 55 parts.

[0102] In the present invention, the monochloroacetic acid-alcohol aqueous solution is preferably a mixture of monochloroacetic acid and an alcohol aqueous solution.

[0103] Based on the mass fraction of the lauryl alcohol, the present invention preferably uses 10 to 15 parts of monochloroacetic acid. In the specific implementation operation, the monochloroacetic acid can be 10 parts, 12 parts or 15 parts.

[0104] Based on the mass fraction of the lauryl alcohol, the present invention preferably uses 15 to 40 parts of alcohol aqueous solution. In the specific implementation operation, the alcohol aqueous solution can be 15 parts, 20 parts, 25 parts, 30 parts or 40 parts.

[0105] In the present invention, the reaction temperature of the etherification reaction is preferably 55-60°C. In the specific implementation, the reaction temperature can be 55°C, 57°C, 59°C or 60°C. The time is preferably 3-5h. In the specific implementation, the time can be 3h, 4h or 5h.

[0106] In the present invention, after the etherification reaction, the process preferably further comprises: solid-liquid separation, drying and pulverizing the obtained product liquid.

[0107] The invention mixes the amidation product with 100-150 parts of water and 3-5 parts of N-vinyl-2-pyrrolidone, adds the carboxymethyl starch, heats to 60-70° C., adds 0.5-1.0 parts of azobisisobutylamidine hydrochloride to initiate polymerization reaction, and obtains composite modified starch.

[0108] Based on the mass fraction of the lauryl alcohol, the present invention preferably uses 100 to 150 parts of water. In the specific implementation operation, the water can be 100 parts, 110 parts, 120 parts, 140 parts or 150 parts.

[0109] Based on the mass fraction of the lauryl alcohol, the present invention preferably uses 3 to 5 parts of N-vinyl-2-pyrrolidone. In the specific implementation operation, the N-vinyl-2-pyrrolidone can be 3 parts, 4 parts or 5 parts.

[0110] In the present invention, the amidation product, water and N-vinyl-2-pyrrolidone are preferably mixed and stirred, and the stirring time is preferably 10 to 30 minutes. In the specific implementation operation, the stirring time can be 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes.

[0111] In the present invention, after adding the carboxymethyl starch, stirring and nitrogen deoxygenation are preferably included. The stirring time is preferably 20 to 40 minutes. In the specific implementation operation, the stirring time can be 20 minutes, 25 minutes, 30 minutes, 35 minutes, 45 minutes or 40 minutes.

[0112] In the present invention, the heating is performed to 60-70°C. In a specific implementation, the temperature after heating can be 60°C, 62°C, 65°C, 68°C or 70°C.

[0113] Based on the mass fraction of the lauryl alcohol, the present invention preferably uses 0.5 to 1.0 parts of azobisisobutylamidine hydrochloride. In the specific implementation, the azobisisobutylamidine hydrochloride can be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1.0 parts.

[0114] In the present invention, the reaction temperature of the polymerization reaction is preferably 60-70°C. In the specific implementation, the reaction temperature may be 60°C, 63°C, 65°C, 67°C or 60°C. The time is preferably 3-5h. In the specific implementation, the time may be 3h, 4h or 5h.

[0115] In the present invention, after the polymerization reaction, the process preferably further comprises: solid-liquid separation of the obtained product liquid, washing with anhydrous ethanol, drying and crushing.

[0116] The composite modified starch obtained by the present invention uses high-amylose starch with an amylose content of more than 40% as a raw material, reduces the content of branched starch that is easily attacked by free radicals, and is beneficial to improving thermal stability; pre-gelatinization (improving starch reaction activity), etherification and grafting modification treatments are carried out on the basis of high-amylose starch, and a large number of carboxyl groups (etherification reaction introduces carboxyl groups in monochloroacetic acid), amide groups, pyrrolidone five-membered rings and lauryl long-chain alkanes are introduced, wherein the carboxyl groups and amide groups give the fluid loss reducer good hydrophilicity and strong adsorption, which can effectively It adsorbs on the surface of solid particles and participates in the formation of mud cake, improving the density and wall protection. The introduction of carboxyl groups increases the charge density of the fluid loss reducer, thereby reducing the influence of the salt shielding effect in high-concentration electrolytes and helping to improve the calcium resistance. The long-chain alkane side chains provide certain hydrophobic properties and can form a hydrophobic film on the surface of the mud cake, further preventing the penetration of water molecules and thus reducing the filtration loss. The five-membered ring of pyrrolidone helps to enhance steric hindrance and inhibit the hydrolysis of the amide group, helping to improve the thermal stability and high-temperature hydrolysis resistance of the fluid loss reducer.

[0117] Based on the mass fraction of the flow pattern regulator, the non-sulfonated calcium chloride water-based drilling fluid includes 1.5 to 3.5 parts of lubricant. In specific implementation operations, the lubricant can be 1.5 parts, 2 parts, 2.5 parts, 3 parts or 3.5 parts.

[0118] Based on 100 parts by mass of the lubricant, the lubricant preferably includes 50-60 parts of oleic acid imidazoline, 20-30 parts of polyethylene glycol borate, 5-20 parts of polyalphaolefin and 5-10 parts of nano polytetrafluoroethylene. Oleic acid imidazoline in the lubricant contains nitrogen heterocycles and long hydrocarbon chains, which can form a strong adsorption lubricating film on the metal surface, thereby reducing the friction coefficient; polyethylene glycol borate can provide a sliding interface and reduce the direct contact between the friction pairs, and has excellent thermal stability due to the presence of borate; polyalphaolefin has good resistance to thermal degradation, is conducive to the formation of a stable lubricating oil film, and is biodegradable; nano polytetrafluoroethylene, as a solid lubricant, can continuously fill the tiny pits on the surface during the friction process, forming a smooth surface and improving the wear resistance of the lubricating film.

[0119] Based on 100 parts by mass of the lubricant, the lubricant preferably includes 50 to 60 parts of oleic acid imidazoline. In specific implementations, the oleic acid imidazoline can be 50 parts, 52 parts, 55 parts, 58 parts or 60 parts. In the present invention, the oleic acid imidazoline is preferably produced by amidation and cyclization of vegetable oleic acid and polyethylene polyamine, which is a well-known technical means in the art; the vegetable oleic acid preferably includes one or more of ricinoleic acid, linoleic acid and palmitoleic acid.

[0120] Based on 100 parts by mass of the lubricant, the lubricant preferably includes 20 to 30 parts of polyethylene glycol borate. In a specific implementation, the polyethylene glycol borate may be 20 parts, 22 parts, 25 parts, 28 parts or 30 parts.

[0121] Based on 100 parts by mass of the lubricant, the lubricant preferably includes 5 to 20 parts of polyalphaolefin. In a specific implementation, the polyalphaolefin may be 5 parts, 10 parts, 15 parts, 17 parts or 20 parts.

[0122] Based on 100 parts by mass of the lubricant, the lubricant preferably includes 5 to 10 parts of nano-polytetrafluoroethylene. In a specific implementation, the nano-polytetrafluoroethylene can be 5 parts, 7 parts, 9 parts or 10 parts.

[0123] Based on the mass fraction of the flow pattern regulator, the non-sulfonated calcium chloride water-based drilling fluid includes 3.5 to 6.5 parts of free radical scavenger. In the specific implementation operation, the free radical scavenger can be 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts or 6.5 parts.

[0124] Based on 100 parts by mass of the free radical scavenger, the free radical scavenger preferably includes 60-80 parts of potassium formate and 20-40 parts of sodium formate. Formate can provide formate ions, which can effectively prevent free radicals from attacking polymer molecules, thereby improving the thermal stability of the polymer. Potassium ions can also assist in improving the hydration inhibition of clay through "embedded" action.

[0125] Based on 100 parts by mass of the free radical scavenger, the free radical scavenger preferably includes 60 to 80 parts of potassium formate. In a specific implementation, the potassium formate can be 60 parts, 65 parts, 70 parts, 75 parts or 80 parts.

[0126] Based on 100 parts by mass of the free radical scavenger, the free radical scavenger preferably includes 20 to 40 parts of sodium formate. In a specific implementation, the sodium formate may be 20 parts, 25 parts, 30 parts, 35 parts or 40 parts.

[0127] Based on the mass fraction of the flow pattern regulator, the non-sulfonated calcium chloride water-based drilling fluid includes 2.5 to 5.5 parts of the plugging agent. In the specific implementation operation, the plugging agent can be 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts or 5.5 parts.

[0128] Based on 100 parts by mass of the plugging agent, the plugging agent preferably includes 40 to 60 parts of potassium humate and 40 to 60 parts of ultrafine calcium carbonate. In the specific implementation, the potassium humate can be 40 parts, 45 parts, 50 parts, 55 parts or 60 parts; the ultrafine calcium carbonate can be 40 parts, 45 parts, 50 parts, 55 parts or 60 parts. Potassium humate is a derivative of natural organic matter, a green environmentally friendly material, and has good adsorption and chelating abilities. It can form a dense film on the surface of the well wall to plug microcracks and pores; ultrafine calcium carbonate, as an environmentally friendly inorganic mineral material, can provide a filling effect; the synergistic effect of the two ensures that the mud cake formed by the plugging agent on the well wall is more dense, has higher mechanical strength and durability, and the plugging agent obtained has less impact on the environment and is suitable for drilling operations requiring high environmental protection.

[0129] Based on 100 parts by mass of potassium humate, the potassium humate preferably includes 60-80 parts of potassium humate and 20-40 parts of potassium humate; in the specific implementation, the potassium humate can be 60 parts, 65 parts, 70 parts, 75 parts or 80 parts, and the potassium humate can be 20 parts, 25 parts, 30 parts, 35 parts or 40 parts.

[0130] Taking the mass fraction of ultrafine calcium carbonate as 100, the ultrafine calcium carbonate preferably includes 20-30 parts of 1000 mesh calcium carbonate, 20-30 parts of 2000 mesh calcium carbonate, 20-30 parts of 3000 mesh calcium carbonate, and 20-30 parts of 4000 mesh calcium carbonate.

[0131] In the specific implementation operation, the 1000 mesh calcium carbonate can be 20 parts, 25 parts or 30 parts; the 1000 mesh calcium carbonate can be 20 parts, 25 parts or 30 parts; the 1000 mesh calcium carbonate can be 20 parts, 25 parts or 30 parts; the 1000 mesh calcium carbonate can be 20 parts, 25 parts or 30 parts.

[0132] Calcium carbonate of different particle sizes (from 1000 mesh to 4000 mesh) is used. These particles can complement each other to form a multi-scale filling structure, effectively blocking cracks and pores of different scales, covering from micron to nanometer scale.

[0133] Based on the mass fraction of the flow pattern regulator, the non-sulfonated calcium chloride water-based drilling fluid includes 0.5 to 2.5 parts of a pH regulator. In a specific implementation, the pH regulator may be 0.5 parts, 1 parts, 1.5 parts, 2 parts or 2.5 parts.

[0134] Based on 100 parts by mass of the pH adjuster, the pH adjuster preferably includes 60 to 80 parts of magnesium oxide and 20 to 40 parts of magnesium hydroxide. In a specific implementation, the magnesium oxide may be 60 parts, 65 parts, 70 parts, 75 parts or 80 parts, and the magnesium hydroxide may be 20 parts, 25 parts, 30 parts, 35 parts or 40 parts. Magnesium oxide and magnesium hydroxide are slightly soluble in water, and can continuously provide an alkaline environment for water-based drilling fluids, and can also alleviate the problem of too fast decrease in alkalinity of drilling fluids at high temperatures.

[0135] Based on the mass fraction of the flow pattern regulator, the non-sulfonated calcium chloride water-based drilling fluid includes 100 parts of water. In the present invention, the water is preferably fresh water or sea water.

[0136] Based on the mass fraction of the flow pattern regulator, the non-sulfonated calcium chloride water-based drilling fluid includes 5 to 35 parts of calcium chloride. In the specific implementation operation, the calcium chloride can be 5 parts, 10 parts, 15 parts, 20 parts, 25 parts or 30 parts.

[0137] In the present invention, the non-sulfonated calcium chloride water-based drilling fluid also includes barite. The present invention uses barite to adjust the density, which can be determined according to the use environment, has flexibility, and is applicable to a wide range of environments.

[0138] In the present invention, the density of the non-sulfonated calcium chloride water-based drilling fluid is preferably 1.0 to 1.8 g / cm 3 In the specific implementation operation, the density of the non-sulfonated calcium chloride water-based drilling fluid can be 1.0 g / cm 3 , 1.1g / cm 3 , 1.3g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3or 1.8 g / cm 3 .

[0139] The present invention also provides a method for preparing the non-sulfonated calcium chloride water-based drilling fluid described in the above technical solution, comprising the following steps:

[0140] The non-sulfonated calcium chloride water-based drilling fluid is obtained by mixing water, calcium chloride, pH regulator, free radical scavenger, fluid loss reducer, plugging agent, flow pattern regulator, lubricant and barite by weight.

[0141] In the present invention, the rotation speed of the stirring and mixing is preferably 8000-12000 r / min. In the specific implementation operation, the rotation speed of the stirring and mixing can be 8000 r / min, 10000 r / min, 11000 r / min or 12000 r / min.

[0142] In the present invention, the mixing of water, calcium chloride, pH regulator, free radical scavenger, fluid loss agent, plugging agent, flow pattern regulator, lubricant and barite preferably includes: mixing water and calcium chloride for 10 to 20 minutes, adding pH regulator and mixing for 5 to 10 minutes, adding free radical scavenger and mixing for 5 to 10 minutes, adding fluid loss agent and plugging agent and mixing for 10 to 20 minutes, adding flow pattern regulator and mixing for 30 to 40 minutes, adding lubricant and mixing for 10 to 15 minutes, adding barite and mixing for 30 minutes. By sequentially distributing and adding each component raw material, a uniformly dispersed and stable drilling fluid is obtained.

[0143] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described in conjunction with specific embodiments below. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Any modification, equivalent replacement, improvement, etc. made to the implementation methods of the present invention based on the technical essence and general principles of the present invention without creative work should be within the scope of protection of the present invention.

[0144] Example 1

[0145] In terms of mass, 100 parts of solvent consisted of 80 parts of anhydrous ethanol and 20 parts of deionized water, which were simply mixed. 100 parts of initiator consisted of 40 parts of potassium persulfate and 60 parts of ammonium persulfate, which were simply mixed.

[0146] The preparation method of modified nano-montmorillonite is as follows:

[0147] 150 parts of solvent were added to a three-necked round-bottom flask by weight, and 1 part of vinyltriethoxysilane was added while stirring. The pH was adjusted to 2 with 0.1 mol / L hydrochloric acid, and the temperature was raised to 50°C after nitrogen was passed to deoxygenate, and the hydrolysis reaction was carried out for 4 hours. 8 parts of nano-montmorillonite were added, and the temperature was raised to 60°C. The reaction was stirred for 10 hours, and the heating was stopped and cooled to room temperature. The solvent was removed by vacuum distillation, and the mixture was washed with anhydrous ethanol for multiple times, dried, and crushed to obtain silane-coupled nano-montmorillonite.

[0148] In a four-necked round-bottom flask, 100 parts of deionized water, 2 parts of itaconic acid, 3 parts of N,N-dimethylacrylamide and 4 parts of N-vinyl-2-pyrrolidone were added, and the mixture was stirred for 10 min. The pH was adjusted to 7 with 0.1 mol / L potassium hydroxide solution, and the obtained silane-coupled nano-montmorillonite was added. After nitrogen was passed to deoxygenate, the temperature was raised to 60°C, and 0.1 parts of initiator were added to react for 4 h. The heating was stopped and the mixture was cooled to room temperature. The solvent was removed by distillation under reduced pressure, and the mixture was washed with anhydrous ethanol for multiple times, dried, and crushed to obtain the modified nano-montmorillonite.

[0149] The preparation method of the composite modified starch is as follows:

[0150] In a four-necked round-bottom flask, 8 parts of lauryl amine were added by weight, the temperature was raised to 60°C with stirring, nitrogen was passed to deoxygenate, 3 parts of maleic anhydride were slowly added to carry out amidation reaction, and the mixture was cooled to room temperature for 4 hours to obtain an amidation product;

[0151] In a three-necked round-bottom flask, 100 parts of ionized water and 30 parts of high-amylose starch with an amylose content of 45% were added by weight, the mixture was heated to 70°C with stirring, cooled to room temperature for 2 hours, 5 parts of sodium hydroxide and 35 parts of 90% ethanol were added under stirring, the mixture was heated to 40°C, 25 parts of monochloroacetic acid solution (prepared by mixing 10 parts of monochloroacetic acid and 15 parts of 90% ethanol) were added, the mixture was heated to 55°C, the mixture was reacted for 3 hours and cooled to room temperature, a precipitate was precipitated with anhydrous ethanol, filtered, dried, and crushed to obtain carboxymethyl starch;

[0152] In terms of mass, 100 parts of deionized water and 3 parts of N-vinyl-2-pyrrolidone were added to a four-necked round-bottom flask containing the amidation product, and the mixture was stirred for 10 minutes. Carboxymethyl starch was added and stirred for 20 minutes. After nitrogen was passed through to deoxygenate, the temperature was raised to 60°C. 0.5 parts of azobisisobutylamidine hydrochloride was added to allow polymerization reaction to occur. The mixture was cooled to room temperature for 3 hours, washed with anhydrous ethanol, dried, and crushed to obtain a composite modified starch.

[0153] In terms of mass fraction, 100 parts of pH regulator consisted of 60 parts of magnesium oxide and 40 parts of magnesium hydroxide, which were simply mixed. 100 parts of flow pattern regulator consisted of 40 parts of modified nano-montmorillonite, 30 parts of nano-hectorite and 30 parts of diutan gum (Jiangsu Aofu Biotechnology Co., Ltd.), which were simply mixed. 100 parts of free radical scavenger consisted of 60 parts of potassium formate and 40 parts of sodium formate, which were simply mixed.

[0154] In terms of mass, 100 parts of plugging agent are composed of 40 parts of potassium humate and 60 parts of superfine calcium carbonate, which are simply mixed. Among them, 100 parts of potassium humate are composed of 60 parts of potassium humate and 40 parts of potassium humate, which are simply mixed. 100 parts of superfine calcium carbonate are composed of 20 parts of 1000 mesh calcium carbonate, 20 parts of 2000 mesh calcium carbonate, 30 parts of 3000 mesh calcium carbonate and 30 parts of 4000 mesh calcium carbonate, which are simply mixed.

[0155] In terms of mass, 100 parts of lubricant are composed of 50 parts of oleic acid imidazoline, 20 parts of polyethylene glycol borate, 20 parts of polyalphaolefin and 10 parts of nano polytetrafluoroethylene, which are simply mixed. Oleic acid imidazoline is produced by amidation and cyclization of vegetable oleic acid and polyethylene polyamine, the vegetable oleic acid used in the production of oleic acid imidazoline is ricinoleic acid, and the polyethylene polyamine used is diethylenetriamine.

[0156] The preparation of non-sulfonated calcium chloride water-based drilling fluid is as follows:

[0157] In terms of mass fractions, 100 parts of fresh water were added to the container, the stirring rate was controlled to be 8000r / min, 10 parts of calcium chloride were added, stirred for 10 minutes, 1 part of pH regulator was added, stirred for 5 minutes, 4 parts of free radical scavenger were added, stirred for 5 minutes, 2 parts of fluid loss reducer and 3 parts of plugging agent were added, stirred for 10 minutes, 0.5 parts of flow pattern regulator were added, stirred for 30 minutes, 2 parts of lubricant were added, stirred for 10 minutes, barite was added, and the density of the drilling fluid was controlled to be 1.10g / cm 3 Stop adding and stir for 30 minutes to obtain a non-sulfonated calcium chloride water-based drilling fluid. The hot rolling temperature of the obtained non-sulfonated calcium chloride water-based drilling fluid is 60°C.

[0158] Example 2

[0159] In terms of mass, 100 parts of the solvent consist of 90 parts of anhydrous ethanol and 10 parts of deionized water. 100 parts of the initiator consist of 40 parts of potassium persulfate and 60 parts of ammonium persulfate.

[0160] The preparation method of modified nano-montmorillonite is as follows:

[0161] 200 parts of solvent were added to a three-necked round-bottom flask by weight, and 3 parts of vinyltriethoxysilane were added while stirring. The pH was adjusted to 5 with 0.1 mol / L hydrochloric acid, and the temperature was raised to 60°C after nitrogen was passed to deoxygenate. The hydrolysis reaction lasted for 6 hours. 12 parts of nano-montmorillonite were added, and the temperature was raised to 70°C. The reaction was stirred for 16 hours. The heating was stopped and cooled to room temperature. The solvent was removed by vacuum distillation. The mixture was washed with anhydrous ethanol for multiple times, dried, and crushed to obtain silane-coupled nano-montmorillonite.

[0162] In a four-necked round-bottom flask, 150 parts of deionized water, 4 parts of itaconic acid, 5 parts of N,N-dimethylacrylamide and 6 parts of N-vinyl-2-pyrrolidone were added, and the mixture was stirred for 30 minutes. The pH was adjusted to 9 with 0.1 mol / L potassium hydroxide solution, and the obtained silane-coupled nano-montmorillonite was added. After nitrogen was passed to deoxygenate, the temperature was raised to 80°C, and 0.2 parts of initiator were added to react for 6 hours. The heating was stopped and cooled to room temperature. The solvent was removed by distillation under reduced pressure, and the mixture was washed with anhydrous ethanol for multiple times, dried, and crushed to obtain the modified nano-montmorillonite.

[0163] The preparation process of composite modified starch is as follows:

[0164] In a four-necked round-bottom flask, 12 parts of lauryl amine were added by weight, the temperature was raised to 70°C with stirring, nitrogen was passed to deoxygenate, 5 parts of maleic anhydride were slowly added, the temperature was raised to 80°C for amidation reaction, and the mixture was cooled to room temperature for 6 hours to obtain an amidation product;

[0165] In terms of mass, 180 parts of ionized water and 40 parts of high amylose starch with an amylose content of 75% were added to a three-necked round-bottom flask, the mixture was heated to 90°C with stirring, cooled to room temperature after 4 hours, 7 parts of sodium hydroxide and 40 parts of 90% ethanol were added under stirring, the mixture was heated to 50°C, 35 parts of monochloroacetic acid solution (prepared by mixing 15 parts of monochloroacetic acid and 20 parts of 90% ethanol) were added, the mixture was heated to 60°C, the mixture was reacted for 5 hours and cooled to room temperature, a precipitate was precipitated with anhydrous ethanol, filtered, dried, and crushed to obtain carboxymethyl starch;

[0166] In terms of mass, 120 parts of deionized water and 5 parts of N-vinyl-2-pyrrolidone were added to a four-necked round-bottom flask containing the amidation product, and the mixture was stirred for 30 minutes. Carboxymethyl starch was added and stirred for 40 minutes. After nitrogen was passed through to deoxygenate, the mixture was heated to 70°C and 1 part of azobisisobutylamidine hydrochloride was added to allow polymerization reaction to occur. The mixture was cooled to room temperature for 5 hours, washed with anhydrous ethanol, dried, and crushed to obtain a composite modified starch.

[0167] In terms of mass fraction, 100 parts of pH regulators are composed of 80 parts of magnesium oxide and 20 parts of magnesium hydroxide. 100 parts of flow pattern regulators are composed of 60 parts of modified nano-montmorillonite, 20 parts of nano-hectorite and 20 parts of diutan. 100 parts of free radical scavengers are composed of 80 parts of potassium formate and 20 parts of sodium formate.

[0168] In terms of mass, 100 parts of plugging agents are composed of 60 parts of potassium humate and 40 parts of superfine calcium carbonate, wherein 100 parts of potassium humate are composed of 80 parts of potassium humate and 20 parts of potassium humate, and 100 parts of superfine calcium carbonate are composed of 30 parts of 1000 mesh calcium carbonate, 30 parts of 2000 mesh calcium carbonate, 20 parts of 3000 mesh calcium carbonate and 20 parts of 4000 mesh calcium carbonate.

[0169] In terms of mass, 100 parts of lubricant are composed of 60 parts of oleic acid imidazoline, 30 parts of polyethylene glycol borate, 5 parts of polyalphaolefin and 5 parts of nano polytetrafluoroethylene, wherein oleic acid imidazoline is produced by amidation and cyclization of vegetable oleic acid and polyethylene polyamine, the vegetable oleic acid used in the production of oleic acid imidazoline is palmitic acid, and the polyethylene polyamine used is diethylenetriamine.

[0170] The preparation of non-sulfonated calcium chloride water-based drilling fluid is as follows:

[0171] In terms of mass fractions, 100 parts of seawater were added to the container, the stirring rate was controlled to be 12000r / min, 30 parts of calcium chloride were added, stirred for 20min, 2 parts of pH regulator were added, stirred for 10min, 6 parts of free radical scavenger were added, stirred for 10min, 3 parts of fluid loss reducer and 5 parts of plugging agent were added, stirred for 20min, 1 part of flow pattern regulator was added, stirred for 40min, 3 parts of lubricant were added, stirred for 15min, barite was added, and the density of the drilling fluid was controlled to be 1.30g / cm 3 Stop adding and stir for 60 minutes to obtain a non-sulfonated calcium chloride water-based drilling fluid. The hot rolling temperature of the obtained non-sulfonated calcium chloride water-based drilling fluid is 80°C.

[0172] Example 3

[0173] In terms of mass, 100 parts of the solvent consist of 85 parts of anhydrous ethanol and 15 parts of deionized water. 100 parts of the initiator consist of 50 parts of potassium persulfate and 50 parts of ammonium persulfate.

[0174] The preparation method of modified nano-montmorillonite is as follows:

[0175] 175 parts of solvent were added to a three-necked round-bottom flask by weight, and 2 parts of vinyltriethoxysilane were added while stirring. The pH was adjusted to 3 with 0.1 mol / L hydrochloric acid, and the temperature was raised to 55°C after nitrogen was passed to deoxygenate, and the hydrolysis reaction was carried out for 5 hours. 10 parts of nano-montmorillonite were added, and the temperature was raised to 65°C, and the reaction was stirred for 13 hours. The heating was stopped and cooled to room temperature, and the solvent was removed by vacuum distillation. The mixture was washed with anhydrous ethanol for multiple times, dried, and crushed to obtain silane-coupled nano-montmorillonite.

[0176] In a four-necked round-bottom flask, 125 parts of deionized water, 3 parts of itaconic acid, 4 parts of N,N-dimethylacrylamide and 5 parts of N-vinyl-2-pyrrolidone were added, by mass, and stirred for 20 minutes. The pH was adjusted to 8 with 0.1 mol / L potassium hydroxide solution, and the obtained silane-coupled nano-montmorillonite was added. After nitrogen was passed to deoxygenate, the temperature was raised to 70°C, and 0.15 parts of initiator were added to react for 5 hours. The heating was stopped and cooled to room temperature. The solvent was removed by distillation under reduced pressure, and the mixture was washed with anhydrous ethanol for multiple times, dried, and crushed to obtain the modified nano-montmorillonite.

[0177] The preparation method of the composite modified starch is as follows:

[0178] In a four-necked round-bottom flask, 10 parts of lauryl amine were added by weight, the temperature was raised to 65°C with stirring, nitrogen was passed to deoxygenate, 4 parts of maleic anhydride were slowly added, the temperature was raised to 70°C for amidation reaction, and the mixture was cooled to room temperature for 5 hours to obtain an amidation product;

[0179] In terms of mass, 130 parts of ionized water and 35 parts of high amylose starch with an amylose content of 60% were added to a three-necked round-bottom flask, the mixture was heated to 80°C with stirring, cooled to room temperature for 3 hours, 6 parts of sodium hydroxide and 55 parts of 90% ethanol were added under stirring, the mixture was heated to 45°C, 52 parts of monochloroacetic acid solution (prepared by mixing 12 parts of monochloroacetic acid and 40 parts of 90% ethanol) were added, the mixture was heated to 58°C, the mixture was reacted for 4 hours and cooled to room temperature, a precipitate was precipitated with anhydrous ethanol, filtered, dried, and crushed to obtain carboxymethyl starch;

[0180] In terms of mass, 120 parts of deionized water and 4 parts of N-vinyl-2-pyrrolidone were added to a four-necked round-bottom flask containing the amidation product, and the mixture was stirred for 20 minutes. Carboxymethyl starch was added and stirred for 30 minutes. After nitrogen was passed through to deoxygenate, the mixture was heated to 65°C and 0.7 parts of azobisisobutylamidine hydrochloride was added to allow polymerization reaction to occur. The mixture was cooled to room temperature for 4 hours, washed with anhydrous ethanol, dried, and crushed to obtain a composite modified starch.

[0181] In terms of mass fraction, 100 parts of pH regulators are composed of 70 parts of magnesium oxide and 30 parts of magnesium hydroxide. 100 parts of flow pattern regulators are composed of 50 parts of modified nano-montmorillonite, 25 parts of nano-hectorite and 25 parts of diutan. 100 parts of free radical scavengers are composed of 70 parts of potassium formate and 30 parts of sodium formate.

[0182] In terms of mass, 100 parts of plugging agents are composed of 50 parts of potassium humate and 50 parts of superfine calcium carbonate, wherein 100 parts of potassium humate are composed of 70 parts of potassium humate and 30 parts of potassium humate, and 100 parts of superfine calcium carbonate are composed of 25 parts of 1000 mesh calcium carbonate, 25 parts of 2000 mesh calcium carbonate, 25 parts of 3000 mesh calcium carbonate and 25 parts of 4000 mesh calcium carbonate.

[0183] In terms of mass, 100 parts of lubricant are composed of 55 parts of oleic acid imidazoline, 25 parts of polyethylene glycol borate, 12.5 parts of polyalphaolefin and 7.5 parts of nano polytetrafluoroethylene, wherein oleic acid imidazoline is produced by amidation and cyclization of vegetable oleic acid and polyethylene polyamine, the vegetable oleic acid used in the production of oleic acid imidazoline is linoleic acid, and the polyethylene polyamine used is diethylenetriamine.

[0184] The preparation of non-sulfonated calcium chloride water-based drilling fluid is as follows:

[0185] In terms of mass fractions, 100 parts of fresh water were added to the container, the stirring rate was controlled to be 10000r / min, 20 parts of calcium chloride were added, stirred for 15min, 1.5 parts of pH regulator were added, stirred for 7min, 5 parts of free radical scavenger were added, stirred for 7min, 2.5 parts of fluid loss reducer and 4 parts of plugging agent were added, stirred for 15min, 0.7 parts of flow pattern regulator were added, stirred for 35min, 2.5 parts of lubricant were added, stirred for 12min, barite was added, and the density of the drilling fluid was controlled to be 1.50g / cm 3 Stop adding and stir for 45 minutes to obtain a non-sulfonated calcium chloride water-based drilling fluid. The hot rolling temperature of the obtained non-sulfonated calcium chloride water-based drilling fluid is 100°C.

[0186] Example 4

[0187] In terms of mass, 100 parts of the solvent consist of 83 parts of anhydrous ethanol and 17 parts of deionized water. 100 parts of the initiator consist of 45 parts of potassium persulfate and 55 parts of ammonium persulfate.

[0188] The preparation method of modified nano-montmorillonite is as follows:

[0189] 160 parts of solvent were added to a three-necked round-bottom flask by weight, and 1 part of vinyltriethoxysilane was added while stirring. The pH was adjusted to 4 with 0.1 mol / L hydrochloric acid, and the temperature was raised to 56°C after nitrogen was passed to deoxygenate, and the hydrolysis reaction was carried out for 4.5 hours. 10 parts of nano-montmorillonite were added, and the temperature was raised to 63°C. The reaction was stirred for 12 hours, and the heating was stopped and cooled to room temperature. The solvent was removed by vacuum distillation, and the mixture was washed with anhydrous ethanol for multiple times, dried, and crushed to obtain silane-coupled nano-montmorillonite.

[0190] In a four-necked round-bottom flask, 120 parts of deionized water, 2 parts of itaconic acid, 4 parts of N,N-dimethylacrylamide and 4 parts of N-vinyl-2-pyrrolidone were added, and the mixture was stirred for 18 minutes. The pH was adjusted to 7 with 0.1 mol / L potassium hydroxide solution, and the obtained silane-coupled nano-montmorillonite was added. After nitrogen was passed to deoxygenate, the temperature was raised to 68°C, and 0.12 parts of initiator were added to react for 4.5 hours. The heating was stopped and the mixture was cooled to room temperature. The solvent was removed by distillation under reduced pressure, and the mixture was washed with anhydrous ethanol for multiple times, dried, and crushed to obtain the modified nano-montmorillonite.

[0191] The preparation method of the composite modified starch is as follows:

[0192] In a four-necked round-bottom flask, 10 parts of lauryl amine were added by weight, the temperature was raised to 63°C with stirring, nitrogen was passed to deoxygenate, 4 parts of maleic anhydride were slowly added, the temperature was raised to 75°C for amidation reaction, and the mixture was cooled to room temperature for 4 hours to obtain an amidation product;

[0193] In a three-necked round-bottom flask, 140 parts of ionized water and 33 parts of high-amylose starch with an amylose content of 50% were added by weight, the mixture was heated to 85°C with stirring, cooled to room temperature after 4 hours, 6 parts of sodium hydroxide and 40 parts of 90% ethanol were added under stirring, the mixture was heated to 46°C, 25 parts of monochloroacetic acid solution (prepared by mixing 10 parts of monochloroacetic acid and 15 parts of 90% ethanol) were added, the mixture was heated to 56°C, the mixture was reacted for 4 hours and cooled to room temperature, a precipitate was precipitated with anhydrous ethanol, filtered, dried, and crushed to obtain carboxymethyl starch;

[0194] In terms of mass, 100 parts of deionized water and 5 parts of N-vinyl-2-pyrrolidone were added to a four-necked round-bottom flask containing the amidation product, and the mixture was stirred for 15 minutes. Carboxymethyl starch was added and stirred for 35 minutes. After deoxygenation by nitrogen, the mixture was heated to 62°C. 0.6 parts of azobisisobutylamidine hydrochloride was added and the mixture was heated to 67°C for polymerization reaction. The mixture was cooled to room temperature for 3 hours, washed with anhydrous ethanol, dried, and crushed to obtain a composite modified starch.

[0195] In terms of mass fraction, 100 parts of pH regulators are composed of 65 parts of magnesium oxide and 35 parts of magnesium hydroxide. 100 parts of flow pattern regulators are composed of 45 parts of modified nano-montmorillonite, 30 parts of nano-hectorite and 25 parts of diutan. 100 parts of free radical scavengers are composed of 65 parts of potassium formate and 35 parts of sodium formate.

[0196] In terms of mass, 100 parts of plugging agents are composed of 45 parts of potassium humate and 55 parts of superfine calcium carbonate, wherein 100 parts of potassium humate are composed of 65 parts of potassium humate and 35 parts of potassium humate, and 100 parts of superfine calcium carbonate are composed of 20 parts of 1000 mesh calcium carbonate, 30 parts of 2000 mesh calcium carbonate, 20 parts of 3000 mesh calcium carbonate and 30 parts of 4000 mesh calcium carbonate.

[0197] In terms of parts by mass, 100 parts of lubricant are composed of 50 parts of oleic acid imidazoline, 30 parts of polyethylene glycol borate, 15 parts of polyalphaolefin and 5 parts of nano polytetrafluoroethylene, wherein oleic acid imidazoline is produced by amidation and cyclization of vegetable oleic acid and polyethylene polyamine, and the vegetable oleic acid used in the production of oleic acid imidazoline is 50 parts of ricinoleic acid and 50 parts of palmitic acid, based on 100 parts by mass, and the polyethylene polyamine used is diethylenetriamine.

[0198] The preparation of non-sulfonated calcium chloride water-based drilling fluid is as follows:

[0199] In terms of mass fractions, 100 parts of seawater were added to the container, the stirring rate was controlled to be 10000r / min, 20 parts of calcium chloride were added, stirred for 10 minutes, 1.0 parts of pH regulator were added, stirred for 5 minutes, 4 parts of free radical scavenger were added, stirred for 10 minutes, 3 parts of fluid loss reducer and 5 parts of plugging agent were added, stirred for 20 minutes, 0.5 parts of flow pattern regulator were added, stirred for 30 minutes, 2 parts of lubricant were added, stirred for 15 minutes, barite was added, and the density of the drilling fluid was controlled to be 1.65g / cm 3 Stop adding and stir for 40 minutes to obtain a non-sulfonated calcium chloride water-based drilling fluid. The hot rolling temperature of the obtained non-sulfonated calcium chloride water-based drilling fluid is 120°C.

[0200] Example 5

[0201] In terms of mass, 100 parts of the solvent consist of 88 parts of anhydrous ethanol and 12 parts of deionized water. 100 parts of the initiator consist of 60 parts of potassium persulfate and 40 parts of ammonium persulfate.

[0202] The preparation method of modified nano-montmorillonite is as follows:

[0203] 200 parts of solvent were added to a three-necked round-bottom flask by weight, and 2 parts of vinyltriethoxysilane were added while stirring, and the pH was adjusted to 3 with 0.1 mol / L hydrochloric acid, and the temperature was raised to 57°C after nitrogen was passed to deoxygenate, and the hydrolysis reaction was carried out for 5 hours, and 12 parts of nano-montmorillonite were added, and the temperature was raised to 68°C, and the reaction was stirred for 15 hours, and the heating was stopped and cooled to room temperature, and the solvent was removed by vacuum distillation, and the silane-coupled nano-montmorillonite was obtained after multiple washing with anhydrous ethanol, drying, and crushing.

[0204] In a four-necked round-bottom flask, 100 parts of deionized water, 3 parts of itaconic acid, 3 parts of N,N-dimethylacrylamide and 5 parts of N-vinyl-2-pyrrolidone were added, by mass, and stirred for 25 minutes. The pH was adjusted to 8 with 0.1 mol / L potassium hydroxide solution, and the obtained silane-coupled nano-montmorillonite was added. After nitrogen was passed through to deoxygenate, the temperature was raised to 75°C, and 0.16 parts of initiator were added to react for 5.5 hours. The heating was stopped and cooled to room temperature. The solvent was removed by distillation under reduced pressure, and the mixture was washed with anhydrous ethanol for multiple times, dried, and crushed to obtain the modified nano-montmorillonite.

[0205] The preparation method of the composite modified starch is as follows:

[0206] In a four-necked round-bottom flask, 10 parts of lauryl amine were added by weight, the temperature was raised to 66°C with stirring, nitrogen was passed to deoxygenate, 4 parts of maleic anhydride were slowly added, the temperature was raised to 75°C for amidation reaction, and the mixture was cooled to room temperature for 5 hours to obtain an amidation product;

[0207] In a three-necked round-bottom flask, 150 parts of ionized water and 30 parts of high-amylose starch with an amylose content of 70% were added by weight, the mixture was heated to 88°C with stirring, cooled to room temperature for 3 hours, 5 parts of sodium hydroxide and 40 parts of 90% ethanol were added under stirring, the mixture was heated to 46°C, 32 parts of monochloroacetic acid solution (prepared by mixing 12 parts of monochloroacetic acid and 20 parts of 90% ethanol) were added, the mixture was heated to 60°C, the mixture was reacted for 5 hours and cooled to room temperature, a precipitate was precipitated with anhydrous ethanol, filtered, dried, and crushed to obtain carboxymethyl starch;

[0208] In parts by mass, 100 parts of deionized water and 5 parts of N-vinyl-2-pyrrolidone were added to a four-necked round-bottom flask containing the amidation product, and the mixture was stirred for 15 minutes. Carboxymethyl starch was added and stirred for 25 minutes. After deoxygenation by nitrogen, the mixture was heated to 68°C, 0.6 parts of azobisisobutyramide hydrochloride was added, the mixture was heated to 70°C, a polymerization reaction occurred, and the mixture was cooled to room temperature for 5 hours. The mixture was washed with anhydrous ethanol, dried, and crushed to obtain a composite modified starch.

[0209] In terms of mass fraction, 100 parts of pH regulators are composed of 80 parts of magnesium oxide and 20 parts of magnesium hydroxide. 100 parts of flow pattern regulators are composed of 55 parts of modified nano-montmorillonite, 25 parts of nano-hectorite and 20 parts of diutan. 100 parts of free radical scavengers are composed of 75 parts of potassium formate and 25 parts of sodium formate.

[0210] In terms of mass, 100 parts of plugging agents are composed of 55 parts of potassium humate and 45 parts of superfine calcium carbonate, wherein 100 parts of potassium humate are composed of 80 parts of potassium humate and 20 parts of potassium humate, and 100 parts of superfine calcium carbonate are composed of 25 parts of 1000 mesh calcium carbonate, 25 parts of 2000 mesh calcium carbonate, 25 parts of 3000 mesh calcium carbonate and 25 parts of 4000 mesh calcium carbonate.

[0211] In parts by mass, 100 parts of lubricant are composed of 60 parts of oleic acid imidazoline, 20 parts of polyethylene glycol borate, 10 parts of polyalphaolefin and 10 parts of nano polytetrafluoroethylene, wherein oleic acid imidazoline is produced by amidation and cyclization of vegetable oleic acid and polyethylene polyamine, and the vegetable oleic acid used in the production of oleic acid imidazoline is 60 parts of ricinoleic acid, 10 parts of linoleic acid and 30 parts of palmitic acid, based on 100 parts by mass, and the polyethylene polyamine used is diethylenetriamine.

[0212] The preparation of non-sulfonated calcium chloride water-based drilling fluid is as follows:

[0213] In terms of mass fractions, 100 parts of fresh water were added to the container, the stirring rate was controlled to be 11000r / min, 30 parts of calcium chloride were added, stirred for 20min, 2 parts of pH regulator were added, stirred for 5min, 5 parts of free radical scavenger were added, stirred for 5min, 2.5 parts of fluid loss reducer and 4 parts of plugging agent were added, stirred for 20min, 0.8 parts of flow pattern regulator were added, stirred for 40min, 3 parts of lubricant were added, stirred for 10min, barite was added, and the density of the drilling fluid was controlled to be 1.80g / cm 3 Stop adding and stir for 50 minutes to obtain a non-sulfonated calcium chloride water-based drilling fluid. The hot rolling temperature of the obtained non-sulfonated calcium chloride water-based drilling fluid is 150°C.

[0214] Comparative Example 1

[0215] On the basis of Example 5, the modified nano-montmorillonite in the flow pattern regulator was replaced with ordinary montmorillonite, and the other contents remained unchanged.

[0216] Comparative Example 2

[0217] Based on Example 5, the fluid loss reducer was replaced with carboxymethyl corn starch, and the other contents remained unchanged.

[0218] Comparative Example 3

[0219] On the basis of Example 5, the fluid loss reducer was replaced by sulfonated lignite, the plugging agent was replaced by sulfonated asphalt, and the rest remained unchanged.

[0220] Comparative Example 4

[0221] On the basis of Example 5, calcium chloride was removed and the amount of barite was adjusted to maintain the density unchanged.

[0222] The drilling fluids obtained in Examples 1 to 5 and Comparative Examples 1 to 4 were evaluated according to GB / T16783.1-2014 "Field Test of Drilling Fluids in Petroleum and Natural Gas Industry Part 1: Water-based Drilling Fluids", and were tested for biodegradability and sulfur content with reference to SY / T7467-2020 "Technical Specifications for Environmental Performance Evaluation of Drilling Fluids" and SN / T 3005-2011 "Elemental Analyzer Determination of Carbon, Hydrogen, Nitrogen and Sulfur Content in Organic Chemicals". The results are shown in Tables 1.1, 1.2 and 2.1, 2.2.

[0223] Table 1.1 Basic properties of drilling fluids obtained in Examples 1 to 5 and Comparative Examples 1 to 4

[0224]

[0225] Table 1.2 Basic properties of drilling fluids obtained in Examples 1 to 5 and Comparative Examples 1 to 4

[0226]

[0227]

[0228] Note: The aging temperature in the high temperature and high pressure filtration loss in Table 1.2 corresponds to the aging temperature in Table 1.1.

[0229] Table 2.1 Inhibition performance of drilling fluids obtained in Examples 1 to 5 and Comparative Examples 1 to 4

[0230]

[0231] Table 2.2 Inhibition performance, lubrication performance and environmental performance of drilling fluids prepared in Examples 1 to 5 and Comparative Examples 1 to 4

[0232]

[0233]

[0234] It can be seen from Examples 1 to 5 that the non-sulfonated water-based drilling fluid based on high concentration calcium chloride has a density of 1.1 to 1.8 g / cm 3 range, and the aging temperature is in the range of 60 to 150°C, all of which have suitable and stable rheology, good filtration control, strong inhibition, low friction and environmentally friendly biodegradable properties. It can be seen from Example 5 and Comparative Example 1 that after the modified nano-montmorillonite is replaced with ordinary montmorillonite, the viscosity of the drilling fluid is significantly reduced, which is not conducive to suspending barite and carrying rock cuttings. At the same time, the filtration loss rate increases significantly, indicating that the synthesized modified nano-montmorillonite has good temperature resistance and calcium resistance and viscosity-increasing properties; It can be seen from Example 5 and Comparative Example 2 that after the synthesized composite modified starch is replaced with conventional carboxymethyl starch, the filtration loss rate of the drilling fluid increases significantly, which is not conducive to water loss and wall building. At the same time, the viscosity decreases and the performance stability is destroyed, indicating that the synthesized composite modified starch has excellent temperature resistance and calcium resistance and filtration loss reduction properties. can; it can be seen from Example 5 and Comparative Example 3 that after the fluid loss reducer and the plugging agent are replaced by the sulfonated material, the fluid loss amount increases instead, while the viscosity decreases, and the obvious sulfur element is detected under the condition of excluding the interference of barite, and the biodegradability decreases significantly, which not only causes the performance to be unstable, but also is not conducive to environmental protection. At the same time, it shows that the non-sulfonated calcium chloride water-based drilling fluid has excellent environmental performance; it can be seen from Example 5 and Comparative Example 4 that after removing calcium chloride, the inhibition performance of the drilling fluid decreases significantly, and the rheology deteriorates significantly after clay pollution, which shows that calcium chloride is the key to the strong inhibition of calcium chloride drilling fluid.

[0235] The five groups of embodiments of the non-sulfonated calcium chloride water-based drilling fluid provided by the present invention, after aging at different densities and different temperatures: have excellent rheological properties, low plastic viscosity, and dynamic-plastic ratios higher than 0.6, showing significant suspension rock-carrying performance; low API and HTHP filtration losses, not exceeding 3.5 mL and 15 mL; extreme pressure friction coefficients significantly lower than 0.1, excellent friction and drag reduction performance, and are suitable for directional well and horizontal well operations; the apparent viscosity increase rate after 40% sodium-based bentonite contamination is significantly lower than 50%, the mudstone rolling recovery rate is higher than 90%, the linear expansion rate is lower than 10%, and the hydration inhibition effect on clay is significant; at the same time, the biodegradation index is greater than 15%, the dry basis sulfur content (excluding calcium chloride and barite) is 0, and the fluid has environmentally friendly biodegradable properties.

[0236] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A non-sulfonated calcium chloride water-based drilling fluid, characterized in that: In terms of mass, it includes 100 parts of water, 5 to 35 parts of calcium chloride, 0.5 to 2.5 parts of pH regulator, 3.5 to 6.5 parts of free radical scavenger, 1.5 to 3.5 parts of fluid loss reducer, 2.5 to 5.5 parts of plugging agent, 0.5 to 1.5 parts of flow pattern regulator, 1.5 to 3.5 parts of lubricant and some barite; The fluid loss reducer is a composite modified starch; The composite modified starch contains carboxyl, amide, pyrrolidone five-membered ring and lauryl; The flow pattern regulator comprises the following components based on 100 parts by mass: 40 to 60 parts of modified nano-montmorillonite, 20 to 30 parts of nano-hectorite and 20 to 30 parts of diutanol; The modified nano-montmorillonite comprises nano-montmorillonite and carboxyl groups, amide groups and pyrrolidone five-membered rings grafted on the surface of the nano-montmorillonite; The lubricant comprises the following components based on 100 parts by mass: 50-60 parts of oleic acid imidazoline, 20-30 parts of polyethylene glycol borate, 5-20 parts of polyalphaolefin and 5-10 parts of nano polytetrafluoroethylene.

2. The non-sulfonated calcium chloride water-based drilling fluid according to claim 1, characterized in that: The free radical scavenger comprises the following components based on 100 parts by mass: 60 to 80 parts by mass of potassium formate and 20 to 40 parts by mass of sodium formate; The pH regulator comprises the following components based on 100 parts by mass: 60 to 80 parts by mass of magnesium oxide and 20 to 40 parts by mass of magnesium hydroxide.

3. The non-sulfonated calcium chloride water-based drilling fluid according to claim 1, characterized in that: The plugging agent comprises the following components based on 100 parts by mass: 40 to 60 parts by mass of potassium humate and 40 to 60 parts by mass of ultrafine calcium carbonate.

4. The non-sulfonated calcium chloride water-based drilling fluid according to claim 3, characterized in that: The potassium humate comprises the following components based on 100 parts by mass: 60 to 80 parts by mass of potassium humate and 20 to 40 parts by mass of potassium humate; The ultrafine calcium carbonate comprises the following components based on 100 parts by mass: 20-30 parts of 1000-mesh calcium carbonate, 20-30 parts of 2000-mesh calcium carbonate, 20-30 parts of 3000-mesh calcium carbonate and 20-30 parts of 4000-mesh calcium carbonate.

5. The non-sulfonated calcium chloride water-based drilling fluid according to claim 1, characterized in that: The oleic acid imidazoline is prepared from vegetable oleic acid and polyethylene polyamine by amidation and cyclization.

6. The non-sulfonated calcium chloride water-based drilling fluid according to claim 1, characterized in that: The preparation of the modified nano-montmorillonite comprises: Mixing 150 to 200 parts of an alcohol aqueous solution and 1 to 3 parts of vinyltriethoxysilane by weight, adjusting the pH to 2 to 5, and performing a hydrolysis reaction to obtain a hydrolysis product; The hydrolyzate is mixed with 8 to 12 parts of nano-montmorillonite to carry out a silane coupling reaction to obtain silane-coupled nano-montmorillonite; 100-150 parts of water, 2-4 parts of itaconic acid, 3-5 parts of N,N-dimethylacrylamide and 4-6 parts of N-vinyl-2-pyrrolidone are mixed, the pH is adjusted to 7-9, the silane-coupled nano-montmorillonite is added, the mixture is heated to 60-70° C., 0.1-0.2 parts of initiator are added, and graft copolymerization is performed to obtain the modified nano-montmorillonite.

7. The non-sulfonated calcium chloride water-based drilling fluid according to claim 1, characterized in that: The preparation of the composite modified starch comprises: 8 to 12 parts of lauryl amine are heated and mixed with 3 to 5 parts of maleic anhydride to carry out an amidation reaction to obtain an amidation product; Mix 30-40 parts of starch and 100-200 parts of water, heat to 70-90°C, cool, add 5-7 parts of alkali and 30-60 parts of alcohol aqueous solution, heat to 40-50°C, add 25-55 parts of monochloroacetic acid-alcohol aqueous solution, carry out etherification reaction, and obtain carboxymethyl starch; The amidation product is mixed with 100-150 parts of water and 3-5 parts of N-vinyl-2-pyrrolidone, the carboxymethyl starch is added, the mixture is heated to 60-70° C., and 0.5-1.0 parts of azobisisobutyramidine hydrochloride is added to initiate polymerization reaction to obtain composite modified starch.

8. The non-sulfonated calcium chloride water-based drilling fluid according to claim 7, characterized in that: The mass content of amylose in the starch is ≥40%.

9. The non-sulfonated calcium chloride water-based drilling fluid according to claim 1, characterized in that: The density of the non-sulfonated calcium chloride water-based drilling fluid is 1.0-1.8 g / cm 3 .

10. The method for preparing the non-sulfonated calcium chloride water-based drilling fluid according to any one of claims 1 to 9, characterized in that: The following steps are involved: The non-sulfonated calcium chloride water-based drilling fluid is obtained by mixing water, calcium chloride, a pH regulator, a free radical scavenger, a fluid loss reducer, a plugging agent, a flow pattern regulator, a lubricant and barite.